PENGARUH JOYFUL LEARNING MELALUI PROBLEM BASED LEARNING TERHADAP KETERAMPILAN PROSES SAINS - Robbin Yama Shita; Arwin Achmad; Berti Yolida (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2015)
The aims of this research was to figure out the effect of using JFL through PBL on Science Process Skill. The design was pretest-posttest non-equivalent group. The samples were X MIA3 and X MIA5 SHS 1 Gadingrejo, chosen by purposive sampling. The quantitative data were obtained from the average score of the test analyzed by t-test and U-test. The qualitative data were Science Process Skill data obtained from the observation sheet and the students questionnaire responses which were analyzed descriptively. The results showed that JFL through PBL could increased the studentss science process skill. It could be seen from the average of N-gain (62.06) in the experiment class which was higher and different significantly than control class (49.99). The result of the average percentage of Science Process Skill observation had a high criteria (79.79%) and most of the students (98%) responded positively to the use JFL through PBL.Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan JFL melalui PBL terhadap KPS. Desain penelitian pretest-postest kelompok tak ekuivalen. Sampel penelitian siswa kelas X MIA3 dan X MIA5 SMA N 1 Gadingrejo dipilih secara purposive sampling. Data penelitian berupa data kuantitatif yang diperoleh dari nilai rata-rata tes yang dianalisis dengan uji-t dan uji-U. Data kualitatif berupa data KPS yang diperoleh dari lembar observasi dan angket yang dianalisis secara deskriptif. Hasil penelitian menunjukkan penggunaan JFL melalui PBL dapat meningkatkan KPS siswa. Terlihat pada rata-rata N-gain kelas eksperimen lebih tinggi (62,06) berbeda signifikan dengan kontrol (49,99). Hasil rata-rata persentase observasi KPS memiliki kriteria tinggi (79,79%) dan sebagian besar siswa (98%) memberikan tanggapan positif terhadap penggunaan JFL melalui PBL.Kata kunci : joyful learning, KPS, PBL, perubahan lingkungan